THE PRESERVATION AND PROMOTION OF BAKHSHI AND MAQOM ART - Ahmedov Elmurod G‘anisherovich (Western European Studies, 2025)
This article explores the interrelation between the Bakhshi (epic) art and the Maqom musical tradition, emphasizing their preservation and promotion within Uzbek diaspora communities. It highlights the cultural, educational, and diplomatic roles of Maqom in strengthening Uzbekistan’s cultural identity abroad. Furthermore, the paper analyzes international cooperation in safeguarding these intangible cultural heritages
Keywords: Bakhshi art; Maqom; diaspora